Crack growth in simulated residual stress fields on tungsten inert gas dressed welded joints: a 2d approach - Ramalho, Armando (2021)
In this paper is presented a 2D finite element model to predict the residual stresses generated by Tungsten Inert Gas (TIG) dressing at the weld toe of a T-joint. The welded T-joints, made of S355AR steel, are obtained by covered electrode process and improved with TIG dressing. The analysis was developed with the MSC.Marc finite element code. The estimated stress field is validated with experimental stress results obtained using X-ray diffraction. Over the estimated residual stress field is simulated the growth of fatigue cracks. The simulation is performed with the virtual crack closure technique, implemented in the MSC.Marc software. The obtained results are compared with the integration solutions of the Paris-Erdogan law, without influence of residual stresses, where the stress intensity factor is obtained using the Mk factor proposed by Bowness and Lee, included in BS 7910 standard. The numerical predictions are also compared with experimental results.